Racial threat and crime control: integrating theory on race and extending its application - Smith, Justin (Critical criminology, 2021)
The racial threat perspective has been applied increasingly to the study of crime control over the past several decades and demonstrates appealing and nuanced arguments for understanding racial bias and disparity. As recent tests of racial threat hypotheses have illustrated, however, the empirical results are mixed. This article seeks to refine the racial threat perspective and addresses methodological limitations. It also explores the application of the racial threat framework to contemporary social landscapes. Discussion concentrates on three distinct issues that seek to develop theory, methodology and epistemology in racial threat research: (1) theoretical integration of the nuances of race relations; (2) relativity of criminal justice systems; and (3) historical and structural racism in crime control.